Comparing Topical Vancomycin Vs Control Procedure Focus On Staphylococcus Event In Spinal Surgery Procedures: A Systematic Review And Meta-Analysis - Puspawan, Ni Putu Eka Gloria (International Journal Labs, 2025)
OBJECTIVE: This study aimed to evaluate the effectiveness of topical vancomycin powder versus standard prophylaxis in preventing gram-positive bacterial infections, specifically Streptococcus species, in spinal surgery patients through systematic review and meta-analysis. DATA SOURCES: A comprehensive search was conducted across PubMed, Cochrane Library, Scopus, and ScienceDirect databases. The search strategy incorporated